Day to Day variation of Ionosphere Electron and Ion Temperature during Great and Severe Geomagnetic Storms - R. Al-Ubaidi, Najat M.; H. Gmayhs, Karam (Iraqi Journal of Science, 2023)
The ionospheric characteristics exhibit significant variations with the solar cycle, geomagnetic conditions, seasons, latitudes and even local time. Representation of this research focused on global distribution of electron (Te) and ion temperatures (Ti) during great and severe geomagnetic storms (GMS), their daily and seasonally variation for years (2001-2013), variations of electron and ion temperature during GMS with plasma velocity and geographic latitudes. Finally comparison between observed and predicted Te and Ti get from IRI model during the two kinds of storm selected. Data from satellite Defense Meteorological Satellite Program (DMSP) 850 km altitude are taken for Te, Ti and plasma velocity for different latitudes during great and severe geomagnetic storms from years 2001 to 2013 according to what is available appeared that there is 22 events for severe and great geomagnetic storms happened during years 2001-2005 only from years selected, from maximum solar cycle 23. From data analysis, in general the temperature of the electron is greater than the temperature of the ion, but there are some disturbances happened during the storm time, in the day there is fluctuation in values of Te and Ti with the value of Ti greater than Te. Through the Dst index, Te and Ti do not depend on the strength of the geomagnetic storm. Plasma velocity variation shows the same profile of Te and Ti variation during the storm time and there is a linear relation between (Te) & (Ti) and plasma velocity. The variation of electron and ion temperature with geographic latitude during severe and great storms appears that as the latitude increases the temperature of ions increases reaches its maximum value approximately 80000K at poles.From comparing the predicted Te and Ti values calculating from IRI model during the great and severe storms with observed values, it’s found that the predicted values from IRI model much less than the observed values and the variation was nonlinear along 24 hours, from this we can conclude that the model must be corrected for Te and Ti for these two kinds of storms.